2019
DOI: 10.1177/1368430219845053
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup contact and willingness for renewed cohabitation in Cyprus: Exploring the mediating and moderating mechanisms

Abstract: One of the major challenges in divided societies is finding ways to overcome geographical partition by increasing readiness for cohabitation in mixed areas. Cyprus has faced a protracted situation of division (between Greek Cypriots and Turkish Cypriots) for the last 44 years. In this paper, we explore the role of intergroup contact (both quantity and quality of contact) in enhancing the willingness of members of these two communities to reestablish cohabitation, using representative survey samples from both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…Trust is particularly relevant in intergroup relations because it implies positive expectations about intentions and others' behavior (Kenworthy et al, 2016) and fosters cooperation between members of different groups (e.g., Ferrin et al, 2008). Numerous studies supported the mediating role of intergroup trust in the relationship between both direct (Çakal et al, 2019;Yucel & Psaltis, 2019) and indirect forms of contact , and attitudinal Paterson et al, 2019) and behavioral intergroup outcomes (Kenworthy et al, 2016;McKeown & Psaltis, 2017;Turner et al, 2013). Relatedly, greater outgroup morality (perceiving the outgroup as honest, trustworthy, and sincere) also explains the effect of positive intergroup contact on outgroup attitudes (Brambilla et al, 2013;Vezzali et al, 2019).…”
Section: Mediators Of Primary and Secondary Transfer Effectsmentioning
confidence: 99%
“…Trust is particularly relevant in intergroup relations because it implies positive expectations about intentions and others' behavior (Kenworthy et al, 2016) and fosters cooperation between members of different groups (e.g., Ferrin et al, 2008). Numerous studies supported the mediating role of intergroup trust in the relationship between both direct (Çakal et al, 2019;Yucel & Psaltis, 2019) and indirect forms of contact , and attitudinal Paterson et al, 2019) and behavioral intergroup outcomes (Kenworthy et al, 2016;McKeown & Psaltis, 2017;Turner et al, 2013). Relatedly, greater outgroup morality (perceiving the outgroup as honest, trustworthy, and sincere) also explains the effect of positive intergroup contact on outgroup attitudes (Brambilla et al, 2013;Vezzali et al, 2019).…”
Section: Mediators Of Primary and Secondary Transfer Effectsmentioning
confidence: 99%
“…But if there is ever going to be a reunification, trust is probably more important than politics and economics for sustainability of a solution even if it involves bizonal bi-communal federation. It is also shown that in the case of Cyprus, increased inter-group contact achieved after the partial removal of borders in 2003 has contributed positively to willingness for renewed cohabitation of the Cypriots (Yücel & Psaltis, 2019). Cyprus negotiations have lacked the consideration of social and psychological impacts of a possible "solution" on Cypriots.…”
Section: Resultsmentioning
confidence: 99%
“…In Cyprus, a measure of self-reported extended cross-group friendship (i.e. a respondent reports having a friend with a cross-group friendship) is associated with warmer feelings toward the outgroup even after controlling for direct contact (Yucel and Psaltis, 2020).…”
Section: Extended Contactmentioning
confidence: 98%
“…Generations of Cypriots have now grown up on a divided island and know no other reality. Perhaps for this reason, survey research has persistently demonstrated that attitudes toward reconciliation are less favorable among the young than among the old in the Greek Cypriot community in Cyprus (''Solving the Cyprus Problem, 2011Problem, , 2013Georgiades, 2007;Sitas et al, 2007;Yucel and Psaltis, 2020). Second, the type of contact that Cypriots engage in upon crossing tends to be shallow and transactional.…”
Section: Intergroup Contact In Cyprusmentioning
confidence: 99%
See 1 more Smart Citation